Pengaruh Pemahaman Akuntansi, Lama Usaha dan Tingkat Pendidikan terhadap Penerapan SAK EMKM dengan Teknologi Informasi sebagai Variabel Moderasi pada UMKM Kota Bogor (Lembaga Pengembangan Kinerja Dosen, 2026)
The purpose of this study was to analyze accounting understanding, business duration, and education level on the implementation of SAK EMKM with information technology as a moderating variable in MSMEs in Bogor City. The applied quantitative approach with a sample of 60 using data analysis program Smart Partial Least Square (PLS) 3.0, a technique classified as Structural Equation Modeling (SEM). The findings and results of this study indicate that accounting understanding, business duration, and education level influence the implementation of SAK EMKM. However, information technology is not able to moderate the influence of accounting understanding, business duration, and education level on the implementation of SAK EMKM. These findings provide further understanding of the factors that influence the implementation of accounting standards in MSMEs, as well as provide important insights for policymakers and MSME actors in efforts to improve compliance with applicable accounting standards. In addition, these results also indicate the need for other approaches to improve the implementation of information technology in MSMEs to support compliance with SAK EMKM. The recommendation from this study is the need for a more holistic approach to increasing the capacity of information technology in MSMEs and improving accounting understanding for business actors at the micro and small levels.